The Past Within Us : An Empirical Approach to Philosophy of History - Martin, Raymond (Book collections on Project MUSE., 2014)
Why do we interpret the past as we do, rather than in some other way or not at all? What is the significance of the fact that we interpret the past? What are historical interpretations? Raymond Martin's approach to these questions transcends both the positivist and humanistic perspectives that have polarized Anglo-American philosophy of history. Martin goes to the source of this polarization by diagnosing a deep-seated flaw in the dominant analytic approach during the period from 1935 to 1975, namely, the emphasis on conceptual analysis rather than the examination of actual historical contr.